2020
DOI: 10.14710/jitaa.45.3.222-233
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characteristic, lactic acid bacteria population, and angiotensin converting enzyme inhibitory activity of traditional fermented beef ”cangkuk” by spontaneous fermentation with the addition of bamboo shoot

Abstract: This research was conducted to examine the chemical properties, lactic acid bacteria (LAB) populationand angiotensin converting enzyme (ACE) inhibitory activity of fermented beef meat with the addition of bamboo shoots. This research used factorial completely randomized design.Factor A was the preparation method of bamboo shoots: chopped, ground, and extracted. Factor B was the ratio of meat and bamboo shoots (B) which was1:0.75,1:1, 1:1,25ratios. The chemical properties observed were total protein, soluble pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Production of the cangkuk according to Mirdhayati [13] with slight modifications (fermentation media and incubation time). Fermented meat was initially prepared as 300 g of small cuts of beef meat for each experimental unit.…”
Section: Production Of the Fermented Meat (Cangkuk)mentioning
confidence: 99%
“…Production of the cangkuk according to Mirdhayati [13] with slight modifications (fermentation media and incubation time). Fermented meat was initially prepared as 300 g of small cuts of beef meat for each experimental unit.…”
Section: Production Of the Fermented Meat (Cangkuk)mentioning
confidence: 99%
“…It was reported that all treatments had ACE-inhibitory activities ranging A c c e p t e d A r t i c l e from 43%-80%. The best ACE-inhibitory activity (80%) was shown by Cangkuk, which was processed by adding ground bamboo shoots and meat at a ratio of 1:0.75 [13]. Traditional fermented foods from Asia have been reported to provide enhanced nutritional content, digestibility, and microbial stability.…”
Section: Introductionmentioning
confidence: 99%